PELUANG DAN KENDALA PENERAPAN TUGAS WILAYAH AL-HISBAH SEBAGAI PENGAWAS PASAR DI PROVINSI ACEH - Hidayatina Hidayatina; Sri Hananan (JURIS (Jurnal Ilmiah Syariah), 2017)
This study aims to analyze the opportunities and constraints in the implementation of the tasks of Wilayatul Hisbah as a market watchdog in Aceh Province. This research uses qualitative method (naturalistic paradigm) with case approach. The result of this research is the opportunity to apply market supervision as part of the task of Wilayatul Hisbah in Aceh by revising the qanun related to the implementation of the WH duties in Aceh. While the obstacles faced are the limitations of Qanun, the lack of understanding of community law, the presence of other market watchdog institutions, and the increasing lack of attention to the economic welfare of WH officers.